Perfect : a pretty little liars novel - Shepard, Sara, 1977- (New York : HarperTeen, 2008)
After their missing friend's body is found and another of their friends commits suicide, four former best friends live in fear of their secrets being exposed by someone who is stalking them via their cell phones.
Originally published: New York : HarperTeen, 2007.
Includes excerpt from: Unbelievable.
Keywords: Secrecy -- Juvenile fiction; Conduct of life -- Juvenile fiction; Friendship -- Juvenile fiction; High schools -- Juvenile fiction; Mystery fiction